1991
DOI: 10.1007/bf00135636
|View full text |Cite
|
Sign up to set email alerts
|

Hybridoma growth and monoclonal antibody production in iron-rich protein-free medium: Effect of nutrient concentration

Abstract: The iron-rich (500 microM ferric citrate) protein-free supplement was added to six different basal media. Cell growth and monoclonal antibody production of a mouse-mouse hybridoma were investigated in 1.3 1 batch cultures performed in a laboratory bioreactor with automatic control of pH and dissolved oxygen concentration. RPMI 1640 served as the control medium. Fortification of the basal medium by balanced mixtures of amino acids and vitamins showed higher positive effect than daily supplementation by glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…This event illustrates how our monitoring system can provide an early warning system against metabolic shift. While we did not attempt to dissect the molecular and metabolic events in this shift we Franek and Dolnikova (1991). c Ozturk and Palsson (1991a).…”
Section: Dissolved Oxygen and Ph Evolution During Cell Passagingmentioning
confidence: 98%
“…This event illustrates how our monitoring system can provide an early warning system against metabolic shift. While we did not attempt to dissect the molecular and metabolic events in this shift we Franek and Dolnikova (1991). c Ozturk and Palsson (1991a).…”
Section: Dissolved Oxygen and Ph Evolution During Cell Passagingmentioning
confidence: 98%
“…We and others have shown that hybridoma and myeloma cells undergo apoptosis under growth-limiting conditions such as those triggered by nutrient exhaustion in batch culture (Franek and Dolnikova, 1991;Mercille and Massie, 1994a,b;Mercille et al, 1994c;Perreault and Lemieux 1993;Singh et al, 1994a,b). Significant improvements in culture longevity and viability of production cell lines have recently been achieved through expression of genes such as Bcl-2 (Fassnacht et al, 1998;Singh et al, 1996;Terada et al, 1997b), Bcl-2 in combination with Bag-1 (Terada et al, 1997a) and adenoviral E1B-19K (Mercille et al, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Also, hybridomas and NS/0 myelomas cultivated in medium devoid of glutamine, glucose, cystine, or oxygen will rapidly die by apoptosis (Mercille and Massie, 1994a,b;Singh et al, 1994), whereas incubation in the presence of elevated levels of metabolic by-products such as ammonia and lactate induces necrotic cell death in these cells. The use of feeding strategies aimed at constantly supplying the cells with sufficient nutrients may considerably delay the induction of apoptotic cell death (Franek and Dolnikova, 1991;Duval et al, 1991;Robinson et al, 1994;Franek, 1995;Franek and ChladkovaSramkova, 1995;DiStephano et al, 1996). While such strategies may indeed improve productivity, they also involve retention of the protein of interest within the culture environment for extended periods of time.…”
Section: Introductionmentioning
confidence: 95%